Human antibody VH domains targeting uPAR as candidate therapeutics for cancers - Chu, Xiaojie; Li, Wei; Hines, Margaret G.; Lyakhov, Ilya; Mellors, John W.; Dimitrov, Dimiter S. (Frontiers in Oncology, 2023)
The high expression of uPAR has been linked to tumor progression, invasion, and metastasis in several types of cancer. Such overexpression of uPAR makes it a potential target for immunotherapies across common cancers such as breast, colorectal, lung, ovarian cancer, and melanoma. In our study, two highaffinity and specific human VH domain antibody candidates, designed as clones 3 and 115, were isolated from a phage-displayed human VH antibody library. Domain-based bispecific T-cell engagers (DbTE) based on these two antibodies exhibited potent killing of uPAR-positive cancer cells. Thus, these two anti-uPAR domain antibodies are promising candidates for treating uPAR positive cancers.